2021
DOI: 10.3390/agriculture11111100
|View full text |Cite
|
Sign up to set email alerts
|

Yield, Economic Benefit, Soil Water Balance, and Water Use Efficiency of Intercropped Maize/Potato in Responses to Mulching Practices on the Semiarid Loess Plateau

Abstract: Increasing agricultural productivity without undermining further the integrity of the Earth’s environmental systems such as soil water balance are important tasks to ensure food security for an increasing global population in rainfed agriculture. The impact of intercropping maize (Zea mays L.) with potato (Solanum tuberosum L.) on yield, land equivalent ratios (LER), water equivalent ratio (WER), water use, energy output, and net economic return were examined under seven planting systems: potato grown solely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The yield difference between the two could be due to the decreased inter and intraspecific competition between potato and faba bean; which resulted from the low plant density of faba bean plants per unit area that allowed potato plants to get a greater domain, which is needed for enhanced yield performance. Similar to the present finding a significant increase in marketable tuber yield by intercropping pattern was reported by different researchers [57,59,[60][61][62]. But in contrast to this report, the finding of (Takim,et al [63]) reported that significant impact of intercropping on unmarketable yield than the marketable yield of sweet potato.…”
Section: Marketable and Unmarketable Tuber Yield (Kg Ha-1)supporting
confidence: 88%
“…The yield difference between the two could be due to the decreased inter and intraspecific competition between potato and faba bean; which resulted from the low plant density of faba bean plants per unit area that allowed potato plants to get a greater domain, which is needed for enhanced yield performance. Similar to the present finding a significant increase in marketable tuber yield by intercropping pattern was reported by different researchers [57,59,[60][61][62]. But in contrast to this report, the finding of (Takim,et al [63]) reported that significant impact of intercropping on unmarketable yield than the marketable yield of sweet potato.…”
Section: Marketable and Unmarketable Tuber Yield (Kg Ha-1)supporting
confidence: 88%
“…Many studies show that intercropping can offer different ecosystem services [ 34 ] because inputs and natural resources are better used to supply nutrients that protect plants against pathogens, pests, and weeds. It can also improve soil fertility, conserve biodiversity and natural habitats, and provide higher yields and more balanced production per unit area due to crop diversification [ 20 , 35 ]. Further research is necessary, but it has been suggested that the types of plants included in an intercropping system could increase or decrease the chemical composition of some bioactive compounds and nutrients.…”
Section: Food Security and Intercropping Systemsmentioning
confidence: 99%
“…Furthermore, farmers may also benefit from socioeconomic gains and greater food security, since multi-cropping can improve yield [ 19 ], which would increase the availability of food or allow them to sell more of their produce [ 20 , 21 , 22 ]. All these characteristics have been widely studied over the years; nevertheless, few studies have analyzed the changes in the quantity and quality of nutrients and phytochemicals that benefit human health due to the interaction of the species involved in intercropping.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of soil moisture during the critical reproductive period of crops has an important impact on their growth and development [12]. Drought and water scarcity, low soil quality, and low rainfall utilization are the primary factors limiting grain production in the Loess Plateau region [13]. Drylands cover over 41% of the world's land area, providing sustenance for approximately 40% of the global population.…”
Section: Introductionmentioning
confidence: 99%